A novel genotype of Hepacivirus bovis identified in reindeer (Rangifer tarandus) in northeastern China - Xu, Wenbo; Wang, Wei; Sui, Liyan; Liu, Nan; Zhao, Yinghua; Liu, Quan (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundHepaciviruses (family Flaviviridae) are significant pathogens affecting both human and animal health. While the hepatitis C virus (Hepacivirus hominis) is extensively studies in humans, related viruses have been identified across various animal species. Bovine hepacivirus (BovHepV) is capable of persistent infection in cattle, facilitating mutation accumulation and recombination events that may generate novel variants. BovHepV has also been found in wild boars and sheep, suggesting a broader host range than previously recognized.MethodsIn this study, metagenomic sequencing was performed on 21 serum samples collected from reindeer (Rangifer tarandus) in Inner Mongolia, China. Two near-complete hepacivirus genomes were identified and designated as Rangifer tarandus hepacivirus (RtHepV) isolates GH01 and GH02. Phylogenetic and p-distance analyses were used to assess genetic relatedness to known hepaciviruses. Recombination detection and host–virus co-evolutionary analyses were also conducted.ResultsAmong 21 reindeer serum samples, the positivity rates of RtHepV GH01 and GH02 were 42.9% (9/21) and 4.8% (1/21), respectively. These isolates shared the highest sequence identities with the BovHepV Bulgaria 9 strain, with nucleotide identities of 68.2% (GH01) and 67.9% (GH02), and amino acid identities of 75.0% (GH01) and 74.8% (GH02). Phylogenetic analysis clustered RtHepV within the Hepacivirus bovis lineage, but in a distinct clade separate from previously reported BovHepV strains. P-distance calculations indicated that RtHepV does not constitute a novel species; instead, it qualifies as a novel genotype within Hepacivirus bovis, as its amino acid identity with other subtypes falls below the 77% threshold. Recombination analyses revealed evidence of genetic exchange between RtHepV and BovHepV strains. Co-evolutionary analyses further highlighted frequent host-switching events within the genus Hepacivirus.ConclusionThis study reports the identification of two novel hepacivirus variants in reindeer from northeastern China, closely related to bovine hepaciviruses. These findings expand the known host range and geographic distribution of Hepacivirus, highlighting its ecological adaptability and the risk of cross-species transmission. The results underscore the potential public and veterinary health implications of hepaciviruses, warranting further investigation into the epidemiology of hepaciviruses.